Menelisik Pesan atau Amanat dari Komik Webtoon Canvas 7 Years Relationship Karya Franncellyn Alexandria - Muhammad Rifki Rahardian Putra; Muhamad Burhanudin (ESTETIK : Jurnal Bahasa Indonesia, 2022)
This study focused on analyzing one of the intrinsic elements in comics, namely the mandate (moral message) offered by the author of the 7 Years Relationship comic published in digital comic media, Webtoon Canvas. The stories developed have a mandate, namely the importance of helping others, repaying the kindness of others who have helped us, and so on. Also in this comic, the author tucked away about the dangers of a child being restrained by his parents to choose his "success" without any compromise or discussing in advance what the child wants in the future. Analyzing this comic uses an analysis of the moral approach to analyze the intrinsic elements of the comic. In addition, the researchers applied this research with note-taking techniques and language translation techniques. This descriptive qualitative research has main purpose of this research is to analyze the morals of the comic storyline 7 years relationship. The benefit of this research is that it makes it easy for readers of the 7 Years Relationship comic to find the meaning and moral message behind the comic story and as a form of implementation and contribution of researchers' scientific studies that can be useful for public literacy materials